Morfologia das glândulas salivares maiores em catetos (pecari tajacu linnaeus,1758) - Oliveira Júnior, Carlos Magno (Universidade Federal Rural do Semi-Árido, 2018)
The American’s wild pigs are endemics to the Americas and execition an important ecological and nutritional role; however, the morphological characteristics of their large salivary glands have not been elucidated, knowing this gap, this work aimed to study the large salivary glands in collared peccaries. The glands were analyzed macroscopically, morphometrically (weight, length, thickness and width) and through light and electron microscopy. The microscopy light followed a methodology for the histochemical characterization of the secretion granules and also immunohistochemical techniques to the membrane carbohydrate’s characterization. The methodological assesment was done in males and females and in animals of different ages. Macroscopically, the collared peccaries have three pairs of larger salivary glands, the parotid, mandibular and sublingual, the last one is divided into two portions, the polistomatic and monostomatic. The parotid is the largest of the glands observed, while the monostomatic portion of the sublingual gland is the smallest. The parotid is located near the ear, covers the entire mandibular and has a triangular shape. The parotid’s morphometric parameters increased as the animal aged. The mandibular is oval and it is on the angle of the mandible. The weight of the mandibular gland decreased along the advancement of the animal's age, while the other morphometric parameters augmented. The polysomntic sublingual is on the floor of the oral cavity, while the monostomatic is in the ventral portion of the mandibular gland. Morphometrically the sublinguals augmented as the animal aged. The parotid is a serous gland, however, young animals synthesized neutral mucins in small amounts, this activity stops in adult animals. The mandibles are mucous and synthesize neutral and acidic mucins in small amounts. The sublinguals are mucous and synthesize acidic and neutral mucins in large quantities. Electron microscopy revealed that the acini were globose, arranged in grape’s cluster shape, adhered to each other through of a mesh of collagen fibers. The ducts were closely related to the acini. The parotid gland ultrastructure revealed the presence of strictly serous acini. The synthesized granules by these cells are very electron-dense. The mandibular glands are mucous. Their cells have numerous electron-forming granules. The sublingual gland is strictly mucosa, with granules, mostly, electrons
Keywords: Imunohistoquímica; desenvolvimento pós-natal; animais silvestres; taiassuídeos; Immunohistochemistry; postnatal development; wild animals; taiassuids; CIENCIAS AGRARIAS::MEDICINA VETERINARIA